Promoting Digital Learning Environment in Arabic Language Education: The Use of Animated Video (AV) For Vocabulary Acquisition among Primary School Students - Mohd Rahimi, Nik; Nasri, Nurfarahin; Samihah, Siti (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2021)
Digitalizing the learning environment receives profound attention for augmenting better learning experiences across subject disciplines, including Arabic language education. By measuring the effectiveness of promoting a digital environment in teaching the Arabic language, this quantitative research investigates the application of animated video (AV) in enhancing Malaysian students’ Arabic vocabulary acquisition. Following a quasi-experimental research design, a group of fourth-grade students (N=46) who studied Arabic as a foreign language was randomly divided into treatment (n=23) and control groups (n=23). The treatment group experienced the use of AV during the teaching and learning sessions, while the control group underwent conventional classroom teaching. The AV contained a variety of multimedia sources to describe and depict Arabic vocabulary accurately. Each group received two 30-minute lessons per week, during which they learned five to seven new words in one lesson. Both groups were later assessed after three weeks, and the scores were analyzed using SPSS Version 20. Findings showed a significant difference between the two groups, t(22)= -3.98, p.001 where the treatment group (M = 86.06, SD = 10.86) recorded higher mean scores in comparison to the control group (M = 80.53, SD = 15.48). This finding provides empirical evidence to suggest AV as an effective technology-supported pedagogy in improving Arabic vocabulary acquisition. The implication of this research informs other important stakeholders, particularly educational technologists and curriculum experts, to advance the application of AV in creating meaningful digital content for learning the Arabic language